Production of alpha 1,3-galactosyltransferase and cytidine monophosphate-N-acetylneuraminic acid hydroxylase gene double-deficient pigs by CRISPR/Cas9 and handmade cloning - Gao, Hanchao; Zhao, Chengjiang; Xiang, Xi; Li, Yong; Zhao, Yanli; Li, Zesong; Pan, Dengke; Dai, Yifan; Hara, Hidetaka; Cooper, David KC; Cai, Zhiming; Mou, Lisha (The Journal of reproduction and development, 2017)
Gene-knockout pigs hold great promise as a solution to the shortage of organs from donor animals for xenotransplantation. Several groups have generated gene-knockout pigs via clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated 9 (Cas9) and somatic cell nuclear transfer (SCNT). Herein, we adopted a simple and micromanipulator-free method, handmade cloning (HMC) instead of SCNT, to generate double gene-knockout pigs. First, we applied the CRISPR/Cas9 system to target alpha 1,3-galactosyltransferase (GGTA1) and cytidine monophosphate-N-acetylneuraminic acid hydroxylase (CMAH) genes simultaneously in porcine fetal fibroblast cells (PFFs), which were derived from wild-type Chinese domestic miniature Wuzhishan pigs. Cell colonies were obtained by screening and were identified by Surveyor assay and sequencing. Next, we chose the GGTA1/CMAH double-knockout (DKO) cells for HMC to produce piglets. As a result, we obtained 11 live bi-allelic GGTA1/CMAH DKO piglets with the identical phenotype. Compared to cells from GGTA1-knockout pigs, human antibody binding and antibody-mediated complement-dependent cytotoxicity were significantly reduced in cells from GGTA1/CMAH DKO pigs, which demonstrated that our pigs would exhibit reduced humoral rejection in xenotransplantation. These data suggested that the combination of CRISPR/Cas9 and HMC technology provided an efficient and new strategy for producing pigs with multiple genetic modifications.